THE EFFECT OF NOISE AND AIR POLLUTION ON THE HEALTH OF EMPLOYEES AND THE COMMUNITY AT THE LARATAMA PLTD - SOUTHWEST SUMBA REGENCY - Yashinta Theedens, Anastasia; Sugiarto, Sugiarto; Sukwika, Tatan; Erislan, Erislan (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
The introduction highlights the dual impact of technological advancements on production and workplace conditions, particularly focusing on the challenges posed by noise pollution and its effects on health, including hearing loss and decreased productivity. Additionally, it emphasizes the need for eco-friendly practices and innovations to manage these environmental and occupational risks. The study examines the impact of noise and air pollution on hearing loss among employees and the surrounding community at PLTD Laratama, using a quantitative research design with a cross-sectional descriptive observational approach, employing observation sheets, questionnaires, and checklists for data collection. Based on the analysis, it was concluded that noise intensity at PLTD Laratama significantly affects hearing disturbances in both employees and the surrounding community. The correlation coefficient for employees (0.671) indicates a strong relationship, while for the community (0.529), it shows a moderate impact. A majority of employee respondents (79.05%) and a significant portion of the community respondents (37.27%) acknowledged the impact of air pollution on health. The study provides valuable insights into how noise pollution affects health, offering recommendations for noise reduction and further research.